(untitled) (Private Law, 2023)
This study’s purpose is to determine the regulation of interfaith marriages, the judges’ legal considerations determine, the position of children in interfaith marriages. This research is a normative legal research method. The results of this study: 1) The regulation for interfaith marriages, namely the Civil Code, HOCI, Staatsblad No.158/1898, Act Number 1 of 1974 concerning Marriage, Presidential Instruction No. 9 of 1991 concerning Islam Law Compilation, Supreme Court Decision Jurisprudence No.1400/K/Pdt/1986, Constitutional Court Decision No. 68/PUU-XII/2014. 2) The judge’s legal consideration is that the applicant has married at the Nusantara Christian Church based on Article 2 Paragraph (2) of Act Number 1 of 1974 and Article 99 KHI. 3) The children resulting from interfaith marriages is an illegitimate children based on Article 42 of the Act Number 1 of 1974 and Article 99 KHI.